Epileptic Seizure Due to Disulfiram Treatment - Erensoy, Habib (Korean J Fam Med, 2019)
Disulfiram has been used for the treatment of alcohol dependence for nearly 65 years and is approved by the Food and Drug Administration. It causes negative reinforcement by accumulating toxic acetaldehyde due to irreversible inhibition of aldehyde dehydrogenase. Disulfiram has very few side effects when taken without alcohol. Epileptic seizure induction is a rare side effect in therapeutic doses, and its mechanism is unknown. We present a patient with a single epileptic seizure which was thought to be due to disulfiram used in the treatment of alcohol dependence. We did not find it ethical to administer disulfiram again because the patient discontinued alcohol use and was afraid of epileptic seizures.